HOUSEHOLD LAXEMAS FOR HOUSEHOLD ITEMS AND EQUIPMENT (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article analyzes household lexemes related to household items and equipment in the epics "Malika Ayyar" and "Bahrom and Gulandom". Among the household items, the things used in the kitchen, the important place of the items in people's lives, their contribution to the manifestation of the people's daily living standard, lifestyle, and most importantly, their ethno-cultural status, are discussed.